Comparison between superficial muscularis propria and deep muscularis propria infiltration in gastric cancer patients: A retrospective cohort study. Issue 29 (July 2016) - Zhang, Wei-Han; He, Du; Chen, Dan-Ni; Li, Ting-Ting; Chen, Xin-Zu; Yang, Kun; Liu, Kai; Zhang, Bo; Chen, Zhi-Xin; Zhou, Zong-Guang; Hu, Jian Kun
Abstract : Abstract: This study aimed to investigate the clinicopathological characteristics and survival outcomes of the subclassification of pT2 gastric cancers according to the depth of tumor involvement. We retrospectively collected clinicopathological data and survival outcomes for pT2 gastric cancer patients from 2006 to 2011. Patients were classified into the superficial muscularis propria (sMP) and deep muscularis propria (dMP) groups. Eighty-nine patients had sMP gastric cancers and 90 patients had dMP gastric cancers. The rates of lymph node metastasis for the sMP and dMP groups were 55.1% and 64.4%, respectively, P = 0.202. The 5-year overall survival (OS) of patients in the sMP group was significantly better than patients in the dMP group (76% vs 61%, P = 0.018). Multivariate analysis demonstrated that the depth of tumor invasion, lymph node metastasis, and postoperative chemotherapy were prognostic risk factors for the OS. For patients with pN0 stage tumor(s), the sMP group had a significantly better 5-year OS rate than the dMP group (92% vs 62%, P = 0.004); for patients with pN1–N3 stages, the 5-year OS rates were comparable between the sMP and dMP groups (64% vs 61%, P = 0.540). The subclassification of pT2 gastric cancer into the sMP and dMP groups can demonstrate different survival outcomes according to the lymph node status. However, the pT2 stage subclassification in the next tumor, node, metastasis (TNM) staging system is pending and requires more large sample size studies to confirm its importance.